Expression of matrix metalloproteinases (MMP-1, MMP-2 and MMP-9) and their inhibitors (TIMP-1 and TIMP-2) in oral submucous fibrosis - Rajendran R; Rajeesh Mohammed P; Shaikh Saleem; Shanthi; Pillai M (Wolters Kluwer Medknow Publications, 2006)
Immunohistochemical staining of formalin fixed, paraffin embedded tissue sections of OSF for MMPs-1,2,9 and their tissue inhibitors TIMP-1and 2 was performed using monospecific antibodies coupled with gelatin zymography (MMP-2 and 9) for measuring enzymatic activity quantitatively and for distinguishing the active from the inactive variants of enzymes. The present study, contrary to earlier reports, recorded statistically significant increase in the levels of stromal expression of MMP-1, MMP-2 and MMP-9 and TIMP-1 and TIMP-2 using monospecific antibodies reacting against tissue antigens.The simultaneous increase in reactivity of MMPs and TIMPs poise difficulty in interpretingthe results of this study. The possible reasons for this result, against the backdrop of existing knowledge, were attempted in this study.